A conceptual model for the adoption of Green Building Technology in the Construction Industry - Md Shaharul, Islam; Abu Bakar, Sade; Mat Saad, Norizan; Uzir, Md. Uzir Hossain; Alam, Syed Shah (Universiti Malaysia Terengganu, 2024)
The construction industry is a significant contributor to the economy in most countries, and it plays a vital role in every country’s economic growth worldwide. The adoption of building technology plays a critical role in providing a healthy environment in the construction industry. Developing nations embrace Green Building Technology (GBT) more slowly than developed nations. This study aims to systematically evaluate the existing literature on the intention to adopt GBTs in terms of theories, contexts, and methodology to analyse the development of research on adopting GBTs over time. Furthermore, based on the synthesis, we have developed a conceptual framework that shows the antecedents and consequences of the adoption of GBTs. In response, this study integrates the Theory of Planned Behaviour (TPB) and the Technology-OrganisationEnvironment (TOE) framework to identify some overlooked influential determinants of GBT and propose insightful research directions in the construction sector. The integrated conceptual framework offers clear justifications for comprehending the behaviour of developers to incorporate GBT in their ongoing and upcoming projects. This study has implications for scholars, policymakers, practitioners, and market researchers seeking answers for the elements that might increase global demand for Green Buildings (GB). This review contributes to the body of knowledge in the green building literature. © 2024 UMT Press. All Rights Reserved.